2013
DOI: 10.1007/s40368-013-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sealing the mesial surfaces of first permanent molars with respect to the status of the distal surfaces of the second primary molars in children at high caries-risk

Abstract: These results suggest that sealing sound surfaces and non-cavitated caries in the proximal mesial surfaces of permanent molar teeth effectively prevents or reduces the progression of caries adjacent to lesions on the distal surfaces of the second primary molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…However, earlier studies have shown promising results when a sealing treatment of early, non-cavitated enamel lesions on proximal posterior surfaces was used in children [Gomez et al, 2005] and young adults [Martignon et al, 2012] for controlling caries progression. Similarly, the same positive results were reported in our first report on this study population 12-14 months following sealing therapy [Gomez et al, 2014]. However, it must be noted that in the therapeutic sealing group, the progression rate of the initial lesions covered with a sealant was very close to being significantly different from that of the paired untreated control surfaces ( p = 0.06).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, earlier studies have shown promising results when a sealing treatment of early, non-cavitated enamel lesions on proximal posterior surfaces was used in children [Gomez et al, 2005] and young adults [Martignon et al, 2012] for controlling caries progression. Similarly, the same positive results were reported in our first report on this study population 12-14 months following sealing therapy [Gomez et al, 2014]. However, it must be noted that in the therapeutic sealing group, the progression rate of the initial lesions covered with a sealant was very close to being significantly different from that of the paired untreated control surfaces ( p = 0.06).…”
Section: Discussionsupporting
confidence: 88%
“…It is interesting to note that the efficacy (ARR; treated vs. paired control) of the preventive sealing increased from 17.1% at the 12-14-month follow-up of this study population [Gomez et al, 2014] to 40.0% after 3.5 years in this group. This result suggests that the preventive sealing applied on a mesial permanent molar abutting a second molar surface with active caries is a very efficacious clinical preventive strategy that can be applied to avoid the development of caries in children at high caries risk.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations